Determination of Solvent Systems for Blade Coating Thin Film Photovoltaics. (30th April 2015) - Tait, Jeffrey G.; Merckx, Tamara; Li, Wenqi; Wong, Cindy; Gehlhaar, Robert; Cheyns, David; Turbiez, Mathieu; Heremans, Paul
Abstract : With lab‐scale solution‐processed thin film photovoltaic (TFPV) devices attaining market relevant efficiencies, the demand for environmentally friendly and scalable deposition techniques is increasing. Replacing toxic halogenated solvents is a priority for the industrialization of solution‐processed TFPV. In this work, a generalized five‐step process is presented for fabricating high‐performance devices from nonhalogenated inks. Resulting from this process, several new solvent systems are introduced based on thiophene, tetralin, 1, 2, 4‐trimethylbenzene, o ‐xylene, and anisole for blade coating of three different diketopyrrolopyrrole‐based (pDPP5T‐2, pPDPP5T‐2S, and P390) bulk heterojunctions applied in organic photovoltaic devices. Devices based on pDPP5T‐2S and P390 attain 5.6% and 6.1% efficiency, respectively, greater than the efficiency either material reached when processed from the halogenated solvent system commonly used. These processes are implemented without post‐deposition annealing treatments or additives. The Hansen solubility parameters of the pDPP5T‐2 material are obtained, and are used, along with wettability data on a variety of substrates, to determine optimum solvent combinations and ratios for deposition. This generalized five‐step process results in new nonhalogenated solvent pathways for the scalable deposition of thin film photovoltaic materials. Abstract : A five‐step process to develop new solvent systems for thin film photovoltaic materials is presented. Suitable inks are determined via Hansen solubility parameters analysis and wettability studies. Several new solvent systems are presented for blade coating diketopyrrolopyrrole‐based materials for organic photovoltaics, achieving >6% efficiency, equivalent to that with halogenated inks.